Mechanical analysis of fiber-reinforced composite running-specific prosthesis using a matrix of TPU or PLA - Davalos Ramirez, Jose Omar (2024)
Running-specific prostheses (RSPs) allow amputees to run competitively and recreationally, offering stability, flexibility, and energy return. Despite advancements, RSP can still improve in materials and manufacturing. This study investigated the mechanical behavior of running-specific prosthesis (RSP) manufactured with a composite of carbon fiber and matrices of thermoplastic polyurethane (TPU) or polylactic acid (PLA). The research objectives were to experimentally determine the most suitable matrix (TPU or PLA) according to mechanical behavior and for the selected matrix to compute the mechanical response for using 8, 10, and 12 carbon fiber layers and a 6, 8, and 10 mm matrix thickness. The matrices were 3D printed and the carbon fiber layers were incorporated by a hand lay-up process. The applied load corresponded to a 60 kg user. Experimental measurements identified that the TPU matrix presents low stiffness compared to the PLA matrix. Numerical analysis indicated a delamination failure in the RSP with 8 layers, whereas with 10 and 12 layers, no failure was observed. No evidence of failure was exhibited for the TPU matrix. Because of its compression capacity, load re- sistance, and the absence of damage, the TPU is suitable for its use in the manufacturing of RSP.